Management of the Liqo' Program to Improve School Literacy at Elementary School Plus Muhammadiyah Brawijaya, Mojokerto City: Manajemen Program Liqo’ untuk Meningkatkan Literasi Sekolah di Sekolah Dasar Plus Muhammadiyah Brawijaya Kota Mojokerto - Suliha, Suliha; Fahyuni, Eni Fariyatul (Universitas Muhammadiyah Sidoarjo, 2023)
A great nation is characterized by a literate and highly civilized society. The Indonesian nation as a large nation must be able to develop a literacy culture as a prerequisite for 21st century life skills. Liqo; as one of the habituation programs at SD Plus Muhammadiya Brawijaya is expected to be able to develop a school literacy culture. This research was conducted with the aim of knowing the liqo' program management system at SD Plus Muhammadiya Brawijaya to improve school literacy. The research method used is descriptive qualitative in the field of management science. The results showed that the management of the liqo' program at SD Plus Muhammadiyah Brawijaya, Mojokerto City was implemented by implementing four management steps, namely Planning, Organizing, Actuating and Evaluation, then applied through the stages of habituation, development and evaluation. teaching. Innovation from the implementation of the liqo' program accompanied by well-organized implementation management is very helpful in improving school literacy culture. The benefits of this research are expected to be a source or reference in the development of the School Literacy program.